An Internet-Based Parent Training With Telephone Coaching on Managing Disruptive Behavior in Children at Special Family Counseling Centers During the COVID-19 Pandemic: Feasibility Study - Saana Sourander; Andre Sourander; Susanna Hinkka-; Terja Ristkari; Marjo Kurki (JMIR Publications, 2022)
BackgroundThere is growing concern about the short- and long-term impacts that the COVID-19 pandemic will have on the mental health and psychosocial well-being of children and families. There are no existing studies about feasibility and outcomes using internet-based parent training programs with telephone coaching for disruptive behavioral problems in childhood during the COVID-19 pandemic in clinical settings. ObjectiveThis study explored how the Strongest Families Smart Website (SFSW) parent training program, with telephone coaching, provided support during the COVID-19 pandemic at specialist family counseling centers in Helsinki, Finland, when restrictions made face-to-face counseling impossible. This study followed the success of a randomized controlled trial (RCT) and its implementation study of the SFSW parent training program by primary care child health clinics. The aim was to improve parenting skills, so that parents could tackle disruptive behavior by developing positive parent-child relationships. It started in May 2020, when the COVID-19 pandemic was at its height in Finland. MethodsIn total, 8 family counseling centers in Helsinki identified 50 referrals aged 3-8 years with high levels of parent-reported disruptive behavioral problems. Child psychopathology and functioning and parental skills and well-being were measured at baseline, posttreatment, and 6 months later using a range of tools. The data were extracted from questionnaires completed by the parents. ResultsWe found that 44 (88%) of the 50 families completed the whole 11-session parent training program. Most of the children (n=48, 96%) had definitive or severe behavioral problems when they were initially screened by the centers, but with those assessed at the 6-month follow-up (n=45, 90%), this dropped to 58% (n=26). There were significant changes from baseline to 6-month follow-up in most of the child psychopathology measures, including the Child Behavior Checklist-Parent Report Form (CBCL) total score (mean change 16.3, SE 3.0, 95% CI 10.2-22.3; P<.001) and externalizing score (mean change 7.0, SE 1.0, 95% CI 4.9-9.0; P<.001). When parenting skills were measured with the Parenting Scale (PS), they showed significant changes from baseline to 6-month follow-up in total scores (mean change 0.5, SE 0.1, 95% CI 0.4-0.7; P<.001). Parents showed significant change in the stress subscore (mean change 3.9, SE 0.8, 95% CI 2.2-5.6; P<.001). Of the parents who filled in the satisfaction questionnaire (n=45, 90%), 42 (93%) reported high satisfaction in the skills and 44 (98%) in the professionalism of the family coaches. ConclusionsThe program proved to be an effective method for improving parenting skills and child psychopathology and functioning. The parents were satisfied with the program, and the dropout rate was exceptionally low. The study shows that the training program could be implemented in specialist clinical settings and during crisis conditions, such as the COVID-19 pandemic.